False negative fetal cell free DNA screening for microdeletion syndromes in the presence of an unbalanced translocation involving monosomy 4p. (7th March 2017) - Qi, Zhongxia; Madaan, Shreshtha; Chetty, Shilpa; Yu, Jingwei; Wiita, Arun P.
Abstract : What's Already Known About This Topic? Aneuploidy screening using cell‐free DNA has recently been expanded to include selected microdeletion syndromes. However, real‐world performance characteristics for the majority of these variants remain unknown. Many primary obstetric providers are unaware of performance limitations and appropriate clinical contexts for ordering these assays. What Does This Study Add? Cell‐free DNA screening using a commercial platform designed to detect chromosomal microdeletions can lead to false negative results, even in the case of a pregnancy at known high risk because of a previous child with 4p‐ syndrome and a paternal translocation carrier. This finding underscores the need for clinician education about the limitations of such testing, the utility of invasive diagnostic testing in similar high‐risk pregnancies, and additional validation of cell‐free DNA assays for microdeletions before further expansion into routine practice.